Pengaruh Perputaran Kas, Perputaran Piutang dan Perputaran Persediaan Terhadap Profitabilitas : Studi pada Perusahaan Food and Beverage di Bursa Efek Indonesia Periode 2017-2022 - Dian Isqamah M; Amiruddin Tawe; Nurman Nurman; Hety Budiyanti; Annisa Paramaswary Aslam (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to determine the effect of cash turnover, accounts receivable turnover and inventory turnover on profitability (ROA) in Food and Beverage companies listed on the IDX during the 2017-2022 period. The data collection method used is secondary data originating from financial reports of Food and Beverage companies registered on the IDX which has a population of 46 companies as research subjects. In this research, the sample was selected using the purposive sampling method and 12 companies were obtained. The analytical method used in this research is multiple linear regression analysis with the help of the SPSS 27 software application. Partial research results show that: 1) Cash turnover has a negative and significant effect on profitability, 2) Receivables turnover has a negative and significant effect on profitability, 3) Inventory turnover has a positive and significant effect on profitability. The research results simultaneously show that cash turnover, accounts receivable turnover and inventory turnover simultaneously influence profitability.